Minimizing Spine Autofusion With the Use of Semiconstrained Growing Rods for Early Onset Scoliosis in Children. Issue 10 (November 2018) - Bouthors, Charles; Izatt, Maree T.; Adam, Clayton J.; Pearcy, Mark J.; Labrom, Robert D.; Askin, Geoffrey N.
Abstract : Background: A new growing rod (GR) design, the semiconstrained growing rod (SCGR), with the added advantage of axial rotation freedom within the components, has been introduced at our center which has been shown to be growth friendly. We hypothesize that the SCGR system would reduce autofusion in vivo, thereby maximizing the coronal plane correction, T1-S1 growth, and the final correction achieved at definitive fusion for children with an early onset scoliosis. Methods: In total, 28 patients had either single or dual 5.5 mm diameter SCGR placed minimally invasively through a submuscular approach. Surgical lengthening procedures occurred approximately every 6 months until the definitive fusion procedure was performed for 18 patients. Scoliosis, kyphosis, and lordosis angles, T1-S1 trunk length, and any complications encountered were evaluated. Results: For the full cohort, before GR insertion, the mean major Cobb curve angle was 72.4 degrees (SD, 18.8; range, 45 to 120), mean T1-S1 trunk length was 282 mm (SD, 59; range, 129 to 365), and at the latest follow-up (mean 6.9 y, SD 3.3, range 2.0 to 13.0), 38.8 degrees (SD, 17.5; range 10 to 90) and 377 mm (SD, 62; range, 225 to 487), respectively. For the subset of 18 patients who have had their final instrumented fusion surgery, the definitive surgery procedure alone produced a correction of the major Cobb curve angle by mean 20.3 degrees (SD, 16.1; P <0.0001), and an increase in the T1-S1 trunk length of mean 31.7 mm (SD, 23.1; P <0.0001). There were 14 complications involving 11 of the 28 patients, giving rise to 5 unplanned surgical interventions and 1 case where GR treatment was abandoned. Conclusions: SCGR patients exhibited statistically significant increase in T1-S1 trunk length and statistically significant decrease in the severity of scoliosis over the course of GR treatment and again, importantly, with the definitive fusion surgery, suggesting that autofusion had been minimized during GR treatment with relatively low complication rates. Level of Evidence: Level IV—case series. Abstract : Supplemental Digital Content is available in the text.